2017
DOI: 10.1177/0963689717728936
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cells Preserve Adult Newborn Neurons and Reduce Neurological Injury after Cerebral Ischemia by Reducing the Number of Hypertrophic Microglia/Macrophages

Abstract: Microglia are the first source of a neuroinflammatory cascade, which seems to be involved in every phase of stroke-related neuronal damage. Two weeks after transient middle cerebral artery occlusion (MCAO), vehicle-treated rats displayed higher numbers of total ionized calcium-binding adaptor molecule 1 (Iba-1)-positive cells, greater cell body areas of Iba-1-positive cells, and higher numbers of hypertrophic Iba-1-positive cells (with a cell body area over 80 μm2) in the ipsilateral ischemic brain regions inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 53 publications
2
18
0
2
Order By: Relevance
“…Recently, Rho GTPases, Rac1 and Cdc42, have been shown to regulate Fc receptor-mediated phagocytosis by controlling the different steps of membrane and actin dynamics, leading to particle engulfment (25,30). Similar to that shown previously (31), MSCs signi cantly changed the morphology of LPS-activated microglia in our study. Our results revealed that the number of branches, junctions, and processes decreased after LPS stimulation and signi cantly increased after MSC co-culture.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Rho GTPases, Rac1 and Cdc42, have been shown to regulate Fc receptor-mediated phagocytosis by controlling the different steps of membrane and actin dynamics, leading to particle engulfment (25,30). Similar to that shown previously (31), MSCs signi cantly changed the morphology of LPS-activated microglia in our study. Our results revealed that the number of branches, junctions, and processes decreased after LPS stimulation and signi cantly increased after MSC co-culture.…”
Section: Discussionsupporting
confidence: 91%
“…Compared with bone marrow-and gingival tissue-derived MSCs, hUC-MSCs have been determined to display the highest immunomodulatory ability (Li et al, 2018). Doses of hUC-MSC between 1 × 10 6 and 4 × 10 6 cells/ml have been deemed effective in a previous study (Chen et al, 2005;Carter and Misra, 2010;Lin et al, 2017). For example, the hUC-MSC concentration of 3 × 10 6 cells/ml was administered in lung disease (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…77 Additionally, IV injection of UC-BSCs (1×10 6 or 4×10 6 ), 1 day after ischemic injury, has been shown to reduce neurological injury in stroke rats. 118 Regarding timing, MSCs administered 3 or 10 days postneonatal hypoxic ischemic injury showed significant improvements in motor behavior, while administration at 17 days showed neither sensorimotor function improvement nor gray/ white matter loss reduction. This suggests a broader treatment window for intranasal MSC delivery, particularly when compared to the current treatment window of 6 hours for therapeutic hypothermia, which is the current standard of care.…”
Section: Optimal Dose Timing and Age Of Stem Cellsmentioning
confidence: 92%